Genome rearrangements, male pregnancy and immunological tolerance – the curious case of the syngnathid immune system - Parker, Jamie; Dubin, Arseny; Roth, Olivia (Frontiers in Marine Science, 2023)
The syngnathid fish group (seahorses, pipefishes and seadragons) is a fascinating lineage associated with an array of evolutionary peculiarities that include diverse morphologies and their unique male pregnancy. These oddities also extend to their immune systems, with a growing body of research highlighting a range of intriguing immunological characteristics and genomic rearrangements, which pose questions regarding their evolutionary history and immune strategies. The functional loss of the major histocompatibility complex class II pathway (MHC II) in the Syngnathus genus and related pathway components in the seahorse (Hippocampus) were two discoveries that initially piqued interest. This sparked discussions concerning immune capabilities, possible facilitative roles in advanced male pregnancy evolution through means of evoking immunological tolerance, as well as a general re-evaluation of how we interpret vertebrate immunological plasticity. Experimental approaches have attempted to clarify further the impact of immune repertoire loss on the efficacy of the syngnathid immune response, specificities regarding the pathways in play during pregnancy as well as the concept of immunological inheritance. The first characterization of the immune cell repertoire of Syngnathus typhle using scRNA-seq represents the latest step to understanding the immune dynamics of these enigmatic fish. This report serves as a review for the immunological insights into the fascinating syngnathid fish group; encompassing their evolutionary history, immune cell populations, links to male pregnancy, and sex specificity, in addition to highlighting future research opportunities in need of investigation.